Mental health of unemployed men in different parts of England and Wales. Issue 6597 (29th August 1987) - Jackson, P R; Warr, P
Abstract : In a study of mental health among unemployed men two contrasting hypotheses about the importance of the local unemployment rate were examined–namely, that very high local unemployment might be associated with either impoverishment or resilience of the community, which would affect health in opposite ways. The mental health of 954 unemployed men registered at 41 unemployment benefit offices in England and Wales was assessed by the general health questionnaire, men in areas of particularly high unemployment being compared with men in areas of moderate and relatively low unemployment. Scores for ill health were significantly lower in areas of particularly high unemployment, even when personal factors known to affect mental health during unemployment were controlled for. These results support the hypothesis that communities with high rates of unemployment develop resilience that is beneficial for the mental health of the unemployed.